Pendekatan Partisipatif dalam Meningkatkan Kesadaran Higiene Industri Pangan dan Penggunaan APD pada UMKM Keripik - Aldyandi, Devlin; Rhomadhoni, Muslikha Nourma; Sunaryo, Merry; Himmah, Nuriyah Faiqotul; Kusumawati, Mia; Farid , Umar; Yusuf, Dimas Syaifullah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Food Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economy, yet hygiene and safety aspects are often overlooked. This study aims to improve MSMEs' understanding of food industry hygiene and the use of Personal Protective Equipment (PPE) through a visual-based educational approach. The study employed a quasi-experimental design, with a Keripik MSME owner in Kemiri Village, Mojokerto Regency as the subject. Data collection methods included observation, interviews, a pre-test, education using posters and videos, and a post-test. The results showed an increase in knowledge scores from 20% in the pre-test to 70% in the post-test, indicating the effectiveness of the educational approach. Despite the increased understanding, resistance to the use of PPE was still found due to comfort concerns. These findings underscore the importance of ongoing education and behavioral approaches in establishing a hygienic and safe work culture in the food MSME sector.